“Ummat” sebagai Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas VIA SDN Kalibanteng Kidul 01 Semarang - Nur Rakhmat (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Learning is a continuous business process in order to get optimal results. Therefore, learning requires sharing creative ways to achieve the best results. As happened at SD Negeri Kalibanteng Kidul 01 Semarang, especially when studying mathematics, the learning outcomes obtained by students were not maximized, that is, there were still 24 out of 40 students who scored below the KKM set, namely 70. This means that only 16 students scored above KKM. Apart from being caused by mathematics being a difficult subject, the learning process is still perfunctory, still conventional and only in class and has not utilized learning media optimally. After going through several processes, we used